Analisis Faktor-Faktor yang Mempengaruhi Impulse Buying pada Konsumen Butik Milopi Shop Pontianak - Dwita Cahyani; Warneri Warneri; Okianna Okianna (Pusat Riset dan Inovasi Nasional, 2025)
This aims to find out and analyze the factors that influence impulse buying among Milopi Boutique consumers in Pontianak City. This research uses qualitative research methods with research subjects as consumers of the Milopi Shop boutique. The sampling technique is purposive sampling with data analysis techniques in this research being data reduction, display and verification. The results of this research show that there are 4 factors that influence impulsive buying: 1. Shopping Lifestyle 2. Fashion Involvement 3. Pre-Decision Stage 4. Post Decision Stage. The shopping lifestyle of Milopi Shop boutique consumers can be categorized into consumptive and hedonistic groups. This is reinforced by the high shopping interest of Milopi Shop boutique consumers with an average of 1-2x a month. Apart from that, their interest in shopping apart from the motif, style or style of good clothes is the quality of the materials used in the clothes. The biggest factor that influences Milopi Shop boutique consumers to shop is their own environment. This environment can include neighbors, friends, friends, artists and TikTok influencers who have the same taste in clothing as them. Sales and discounts also play a big role in the high level of impulsive buying at the Milopi Shop Boutique. After purchasing the goods, Milopi shop boutique consumers did not check/evaluate the goods again for fear of changing their minds.